2017
DOI: 10.1111/1468-4446.12235
|View full text |Cite
|
Sign up to set email alerts
|

Social closure, micro‐class immobility and the intergenerational reproduction of the upper class: a comparative study

Abstract: This article assesses how processes of social closure enhance intergenerational immobility in the regulated professions and thus promote persistence at the top of the occupational hierarchy. We compare four European countries (GB, Germany, Denmark and Sweden) that differ considerably in their degree of professional regulation and in their broader institutional arrangements. We run log-linear and logistic regression models on a cumulative dataset based on three large-scale surveys with detailed and highly compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 17 publications
3
17
0
1
Order By: Relevance
“…Table 2 summarises the findings. The study confirms that deliberate social closure is still relevant in the labour market (see Ruggera and Barone, 2017;van de Werfhorst, 2011). The findings confirm the social closure theories described earlier, but fundamentally extend these theories by demonstrating how within-occupational forms of closure fundamentally shape labour market transitions.…”
Section: Level Of Educational Congestionsupporting
confidence: 85%
“…Table 2 summarises the findings. The study confirms that deliberate social closure is still relevant in the labour market (see Ruggera and Barone, 2017;van de Werfhorst, 2011). The findings confirm the social closure theories described earlier, but fundamentally extend these theories by demonstrating how within-occupational forms of closure fundamentally shape labour market transitions.…”
Section: Level Of Educational Congestionsupporting
confidence: 85%
“…As previous studies have demonstrated when, the origin-destination association is analysed from a comparative perspective, it becomes apparent that professionals' social reproduction is a deeply pervasive phenomenon; it is prevalent in Germany and Denmark (Ruggera & Barone, 2017). In Italy, although professional regulation is even stricter than it is in Germany, occupational specificity levels are comparable (Ruggera, 2016).…”
Section: Declining Hypothesesmentioning
confidence: 90%
“…male-bread winner model) and the advantages related to regulated professions in Italy, fathers' professional position is expected to be relevant for daughters' labour market outcomes as-even if at a broader class level (e.g. Ruggera & Barone, 2017). At the aggregate level, commonly used to study the origin-education relationship, social origin corresponds to Erikson and Goldthorpe's (1992) class scheme: higher service class I, including: higher entrepreneurs, higher managers and high level professionals; low service class II; skilled white collars (IIIa); routine non-manual (IIIb); selfemployed with no or few employees (IVab); farmers (IVc); skilled and unskilled manual working class (V-VI-VIIab).…”
Section: Data Variables and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…No obstante, si los datos se ponen en perspectiva, este hecho no es algo tan infrecuente. Para empezar, porque los estudiosos de la estratificación social saben bien que esto es algo relativamente común en las ocupaciones de elevado estatus socio-económico, ya que existen mecanismos de cierre social que favorecen el hecho de que las profesiones se transmitan de una generación a la siguiente (Aina y Nicoletti, 2014;Ruggera y Barone, 2017). En segundo lugar, porque estudios pioneros en otros países como Estados Unidos (Prewit et al, 1966) o Canadá (Kornberg et al, 1969) sugieren que la proporción de representantes con parientes que también se dedicaban a la política puede estar por encima de los que se encuentran en el caso español.…”
Section: Vocación Y Carrera Políticaunclassified